2013
DOI: 10.3390/cells2030460
|View full text |Cite
|
Sign up to set email alerts
|

Methylcellulose Based Thermally Reversible Hydrogel System for Tissue Engineering Applications

Abstract: The thermoresponsive behavior of a Methylcellulose (MC) polymer was systematically investigated to determine its usability in constructing MC based hydrogel systems in cell sheet engineering applications. Solution-gel analyses were made to study the effects of polymer concentration, molecular weight and dissolved salts on the gelation of three commercially available MCs using differential scanning calorimeter and rheology. For investigation of the hydrogel stability and fluid uptake capacity, swelling and degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
59
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 53 publications
2
59
0
1
Order By: Relevance
“…Although the gelation of MC has been extensively studied by various analytical techniques (NMR, differential scanning calorimetry, IR attenuated total reflectance spectroscopy, small-angle neutron scattering, static and dynamic light scattering, and rheology) and the researchers have proposed different gelation mechanisms, the specific molecular interactions that govern this process is still unclear. However, the results of various studies, which were in good agreement one with another, indicated several factors and/or phenomena which play an important role in the gelation of MC [24,[51][52][53][54][55][56][57][58][59][60][61][62][63][64]:…”
Section: Colloidal Dissolution and Gelation As Processes Involved Inmentioning
confidence: 56%
“…Although the gelation of MC has been extensively studied by various analytical techniques (NMR, differential scanning calorimetry, IR attenuated total reflectance spectroscopy, small-angle neutron scattering, static and dynamic light scattering, and rheology) and the researchers have proposed different gelation mechanisms, the specific molecular interactions that govern this process is still unclear. However, the results of various studies, which were in good agreement one with another, indicated several factors and/or phenomena which play an important role in the gelation of MC [24,[51][52][53][54][55][56][57][58][59][60][61][62][63][64]:…”
Section: Colloidal Dissolution and Gelation As Processes Involved Inmentioning
confidence: 56%
“…The precise gelation mechanism needs to be considered and adapted accordingly when electrospraying with different materials. For example, pectin responds to pH depending on its origin [39] , methylcellulose responds to temperature [40] , and alginate is UV responsive as demonstrated by Guo et al who showed an increasing porosity in 3-D alginate scaffolds when exposed to ultrasound leading to improved growth of chondrocytes [41] . Thus, microcapsule and microcarrier preparation can vary depending on material and desired physical parameters for specific applications.…”
Section: Ehd Compatible Biomaterialsmentioning
confidence: 99%
“…Проводимые за рубежом и в России разработки матриксов (скаффолдов) как носителей кле-ток при трансплантации можно разбить на две большие группы: создание матриксов из биостабильных матери-алов (биостабильные синтетические полимеры, спла-вы, керамика) и из биодеградируемых материалов ис-кусственного или природного происхождения [35] Наиболее часто в биопечати в качестве скаффол-дов используют гидрогели, в состав которых могут вхо-дить следующие вещества: альгиновая кислота или альгинат [36,37], хитозан [38], желатин [39], гиалуроно-вая кислота [40,41], агароза [42], коллаген [43,44], плю-роник [45], матригель [46], метилцеллюлоза [47,48], метилцеллюлоза [49], фибрин [50].…”
unclassified